1989
DOI: 10.1128/aem.55.4.1026-1028.1989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyethylene glycol-electrolyte lavage solution on intestinal microflora

Abstract: The bacterial flora of colonic aspirates taken after oral administration of a polyethylene glycol-electrolyte lavage solution to patients undergoing colonoscopy was analyzed by standard bacteriological methods and DNA hybridization techniques. The data were compared with those for normal feces collected from the same patients the day before treatment. The results indicate that the bacterial composition of feces differs from individual to individual but is not altered by the oral intake of a polyethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Essentially, the studies investigating the effect of PEG 3350 on intestinal flora were performed at a high dose, similar to that used for colonic lavage. Some of these studies showed no significant difference between prelavage and postlavage bacterial cultures, 24,25 while Drago et al showed the decreased density of Lactobacillus and increased density of proteobacteria, which is known to cause severe diarrheal attacks. 6 Contrary, rikenellaceae had been shown to decrease in pediatric patients with NAFLD and increased in individuals who had colonic lavage with PEG.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, the studies investigating the effect of PEG 3350 on intestinal flora were performed at a high dose, similar to that used for colonic lavage. Some of these studies showed no significant difference between prelavage and postlavage bacterial cultures, 24,25 while Drago et al showed the decreased density of Lactobacillus and increased density of proteobacteria, which is known to cause severe diarrheal attacks. 6 Contrary, rikenellaceae had been shown to decrease in pediatric patients with NAFLD and increased in individuals who had colonic lavage with PEG.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are known to modulate the composition of the intestinal microbiota in both quantitative and qualitative terms (Dethlefsen and Relman, 2011; Ianiro et al, 2016), and their therapeutic efficacy has been demonstrated in non-infectious diseases such as IBS and hepatic encephalopathy (Ianiro et al, 2016). In addition to antibiotics, bowel lavage will reduce the number of intestinal bacteria and affect the microbial ecosystem temporarily (Morotomi et al, 1989; Jalanka et al, 2015). Although recent studies have shown that donor microbiota and specific donor-derived strains colonize the recipient after FMT (Jalanka et al, 2016; Li et al, 2016; Allegretti et al, 2019), it remains unclear whether donor strain engraftment is a prerequisite for the therapeutic efficacy of FMT in rCDI.…”
Section: Introductionmentioning
confidence: 99%